MODEL PENGELOLAAN SMS GATEWAY PENDUKUNG LAYANAN INFORMASI BAGI ANGGOTA FITNES HORISON DI KOTA SEMARANG (Information Technology and Telematics, 2015)
Abstract : Gym  developments  in  Indonesia  begins  with  a  special training  for  athletes  and not  for  the  public. Equipment was not as complete and as good as in the modern Gym. Modern fitness began  to develop at certain hotels and a  local  fitness center. Not only that, a small fitness center began to emerge. The use of cell phones that were once just to make voice calls only,  at  this  time  is  more  dominant  to  the  use  of  short message  service SMS  (Short Message Service) because  they are more  comfortable and  the purpose of  communication  is achieved. The number of members  in a  fitness center  fitness make  use  of  fitness  equipment  should  be  organized  and  on schedule so that all members can use the equipment. This  study  aims  to  create  a  model  that  is  capable  of managing  information  services  for members Fitnes Horison Semarang City by using SMS Gateway. With  the SMS Gateway Support Services Information  for Members  Fitnes  Horison  Semarang  City  can  provide information  in  the  form  of  a  thank  you  payment,  payment validity  period  and  dissemination  of  information  in  the Horizon Fitnes. Kata Kunci : SMS Gateway, Support Services, Fitness Horison Semarang